Clinical characteristics of patients with different subtypes of gestational diabetes mellitus: research results - N. I. Volkova; I. Y. Davidenko; Y. S. Degtiareva; Y. A. Sorokina; V. V. Avrutskaya (Сахарный диабет)
INTRODUCTION. Gestational diabetes mellitus (GDM) is one of the most common diseases during pregnancy. To date, there is evidence showing that not all pregnant women with GDM have the same risks of developing complications. Identification of patients at increased risk of complications may be necessary given the increasing prevalence of GDM. The need for a more detailed study of GDM subtypes to identify patients at high risk of complications formed the basis of the study.PURPOSE. Determination of anamnestic, phenotypic, and biochemical characteristics of GDM subtypes for the further development of diagnostic and treatment methods.MATERIALS AND METHODS. A single-center observational prospective study was carried out at the Department of Internal Medicine No. 3 of the Rostov State Medical University of the Ministry of Health of the Russian Federation in the period from April 2021 to August 2022. The study included 130 pregnant women. Participants underwent an oral glucose tolerance test with 75 g of glucose assessing fasting, 60- and 120-minutes venous plasma glucose and insulin levels, and fasting blood was drawn to determine levels of main lipid metabolism indicators, apolipoprotein A, and apolipoprotein B, adiponectin, leptin and omentin, glycated hemoglobin, C-reactive protein. All study participants underwent anamnesis and physical examination with assessment of body mass index (BMI), blood pressure, signs of acanthosis nigricans, and a questionnaire. When GDM was detected, the Matsuda index was calculated: >50th percentile in comparison with the values of pregnant women without carbohydrate metabolism disorders, the patient belonged to the group of GDM with β-cell dysfunction; <50th percentile - to the GDM group with predominant insulin resistance.RESULTS AND DISCUSSION. Women with GDM and insulin resistance were older, had a higher BMI before pregnancy, greater weight gain, and more often had signs of acanthosis nigricans compared to patients with GDM and β-cell dysfunction. Also, when comparing patients with different subtypes of GDM, numerous biochemical differences and lifestyle features were identified..CONCLUSION. We demonstrated pronounced anamnestic, phenotypic, and biochemical heterogeneity in patients with different subtypes of GDM, which may become the basis for the further development of verification of GDM subtypes.